Peran Pekerja Sosial Sebagai Konselor Terhadap Korban Pelecehan Seksual Anak Dibawah Umur - Muhammad Cholid; Ati Kusmawati (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
This article discusses the role of social workers as counselors in situations of sexual abuse against minors. The discussion in this page is based on literature reviews from numerous reading sources, such as journals and books, which are used to elucidate beliefs concerning the function of social workers. This research method employs a qualitative descriptive approach, namely research that describes natural situations. This technique is intended to define the general role of social workers as counselors to victims of sexual assault against children. The surge in sexual assault against children highlights the significance of giving counseling to children who have been victims of sexual violence. Research findings reveal that social workers play an essential role in coping with challenges.